High Performance Electrochemical Capacitor Based on Activated Carbon Derive from Palm Oil Kernel Shell - Nurul Khairiyyah, Mohd Zain; Izan Izwan, Misnon; Radhiyah, Abd Aziz; Mohd Hasbi, Ab. Rahim; M. M., Yusoff; Rajan, Jose (2013)

(untitled)
Carbon, in a number of polymorphic forms such as amorphous carbon, activated carbon, carbon fibers, carbon nanotubes, and graphere, is used as energy a storage material due to several reasons including low cost, abundant, stability and scalability.